Boys and road rage: Driving related violence and aggression in Western Australia. - Roberts, Lynne; Indermaur, David (Australian Academic Press Pty Ltd, 2005)
This article reports on the results of a population survey of 1208 West Australian drivers designed to measure the prevalence of drivingrelated violence and aggression as well as perceptions of these behaviours. A clear distinction is made between driving-related violence (restricted to criminal acts of violence, threats of violence and vehicle damage) and other aggressive driving behaviours. Although the majority of survey respondents had experienced some form of aggressive driving behaviour, only 13% reported ever being a victim of driving-related violence. However, 17% of respondents believed they were likely, or very likely, to be a victim of driving-related violence within the coming year. More than two thirds of respondents thought their likelihood of being a victim of driving-related violence had increased over the past 10 years. Both aggressive driving behaviours and driving-related violence were typically perpetrated by young males against other males. The article concludes with a discussion of the masculinist characteristics of road rage and what this implies for the prevention of this crime.